2022
DOI: 10.3389/fphar.2022.878092
|View full text |Cite
|
Sign up to set email alerts
|

A Prescribing Cascade of Proton Pump Inhibitors Following Anticholinergic Medications in Older Adults With Dementia

Abstract: Introduction: Prescribing cascade refers to use of a medication to treat a drug-related adverse event. Prescribing cascades increase medication use, cost, and risk of adverse events.Objective: Our objective was to use administrative health data to identify whether use of medications from the anticholinergic cognitive burden scale was associated with proton pump inhibitor (PPI) prescribing consistent with a prescribing cascade in older adults with dementia.Method: The cohort was comprised of Nova Scotia Seniors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…These results suggested that GSAM may be a risk factor for prescribing cascades. It has been suggested that dementia may be caused by a prescribing cascade of therapeutic medications 17,18 . A higher prevalence of dementia (12.1%) was observed in participants subjected to a prescription cascade than in those prescribed medications specifically for GS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that GSAM may be a risk factor for prescribing cascades. It has been suggested that dementia may be caused by a prescribing cascade of therapeutic medications 17,18 . A higher prevalence of dementia (12.1%) was observed in participants subjected to a prescription cascade than in those prescribed medications specifically for GS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that dementia may be caused by a prescribing cascade of therapeutic medications. 17,18 A higher prevalence of dementia (12.1%) was observed in participants subjected to a prescription cascade than in those prescribed medications specifically for GS. Our result supports those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Use of medications from the following four classes; antidepressants (tricyclic antidepressants, selective serotonin reuptake inhibitors (SSRIs), bupropion and trazodone), cholinesterase inhibitors, antipsychotics (first- and second-generation), benzodiazepines, and nonbenzodiazepine benzodiazepine receptor agonist hypnotics (z-drugs)) was reported. Psychoactive medications from these classes were chosen as those more commonly used to manage behavioural symptoms of dementia and this data were available for analysis from another cohort study [ 29 31 ]. Data were not available for some other medications that could have been relevant to the analysis, including the atypical antidepressant mirtazapine, the selective norepinephrine reuptake inhibitor duloxetine, and anticonvulsants.…”
Section: Methodsmentioning
confidence: 99%
“…Psychoactive medications from these classes were chosen as those more commonly used to manage behavioural symptoms of dementia and this data were available for analysis from another cohort study. [28][29][30] Data were not available for some other medications that could have been relevant to the analysis, including the atypical antidepressant mirtazapine, the selective norepinephrine reuptake inhibitor duloxetine, and anticonvulsants. Medication use was approximated from the dispensing data recorded in the Seniors' Pharmacare database (PHARM).…”
Section: Psychoactive Medication Polypharmacy Identi Cationmentioning
confidence: 99%